2012
DOI: 10.1029/2011jd016646
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term aerosol measurements in Gran Canaria, Canary Islands: Particle concentration, sources and elemental composition

Abstract: .[1] There are very few sets of long-term measurements of aerosol concentrations over the North Atlantic Ocean, yet such data is invaluable in quantifying atmospheric dust inputs to this ocean region. We present an 8-year record of total suspended particles (TSP) collected at three stations on Gran Canaria Island, Spain (Taliarte at sea level, Tafira 269 m above sea level (a.s.l.) and Pico de la Gorra 1930 m a.s.l.). Using wet and dry deposition measurements, the mean dust flux was calculated at 42.3 mg m À2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
59
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 103 publications
8
59
2
Order By: Relevance
“…Between t16 and t22, easterly winds transported dust from the Sahara desert to the Canary Islands and the experiment site. Such dust events regularly occur in the study area and can sometimes constitute a considerable source for input of trace nutrients, such as iron (Gelado-Caballero et al, 2012). The total dry deposition flux from t16 to t22 was estimated at ∼230 mg m −2 , which is comparable to other weak dust events in the region (Gelado-Caballero, Personal Communication).…”
Section: Oligotrophic Phasementioning
confidence: 59%
“…Between t16 and t22, easterly winds transported dust from the Sahara desert to the Canary Islands and the experiment site. Such dust events regularly occur in the study area and can sometimes constitute a considerable source for input of trace nutrients, such as iron (Gelado-Caballero et al, 2012). The total dry deposition flux from t16 to t22 was estimated at ∼230 mg m −2 , which is comparable to other weak dust events in the region (Gelado-Caballero, Personal Communication).…”
Section: Oligotrophic Phasementioning
confidence: 59%
“…These ratios have previously been found to act as useful finger prints of source region (Chiapello et al, 1997;Gelado-Caballero et al, 2012;Guieu et al, 2002;Lafon et al, 2006;Moreno et al, 2006). Additionally, the elemental ratios of have been observed by others (Chiapello et al, 1997).…”
Section: Elemental Ratiosmentioning
confidence: 92%
“…Aerosol measurements over the tropical Northeast Atlantic are limited in both spatial and temporal coverage, with observations restricted to occasional research cruises (Baker et al, 2006;Sarthou et al, 2003;Sholkovitz et al, 2012), land-based observations from the Canary Islands (Gelado-Caballero et al, 2012;Neuer et al, 2004) and a limited number of studies on Cape Verde (e.g. Chiapello et al, 1997;Chiapello et al, 1995;Fomba et al, 2013).…”
mentioning
confidence: 99%
“…The main emission sources of Pb, Cu, Zn, Ni, and Cd are mobile sources, including gasoline and diesel vehicles (Pacyna and Pacyna, 2001). A previous study suggested that Pb, Cd, Ni, and Zn originate from a common local source (Gelado-Caballero et al, 2012). Although Minguillòn et al (2012) stated high Pb concentrations might be related with thermal processes, they also concluded a factor associated with Zn and Cu from road traffic.…”
Section: Introductionmentioning
confidence: 98%